1995
DOI: 10.1111/j.1547-5069.1995.tb00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Nurse‐Expressed Empathy, Patient‐Perceived Empathy and Patient Distress

Abstract: It is increasingly important that nursing care be associated with measurable patient outcomes. A correlational study examined relationships between nurse-expressed empathy and two patient outcomes: patient perceived empathy and patient distress. Subjects (N = 140) were randomly selected from RNs and patients on medical and surgical units in two urban, acute care hospitals. Nurse-subjects (N = 70) completed two measures of nurse-expressed empathy: the Behavioral Test of Interpersonal Skills and the Staff-Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 21 publications
0
72
2
3
Order By: Relevance
“…However, this synthesis has shown that HCPs often do not consider the reproductive potential of women with T2DM and in some cases may hold negative views of the women, particularly in relation to weight, prejudicing discussions about pregnancy 24. Hence, HCPs should be supported in developing consultation skills that elicit women’s pregnancy intentions, allow them to voice any concerns or anxieties, and foster a productive relationship for the delivery of PPC 32,33…”
Section: Resultsmentioning
confidence: 99%
“…However, this synthesis has shown that HCPs often do not consider the reproductive potential of women with T2DM and in some cases may hold negative views of the women, particularly in relation to weight, prejudicing discussions about pregnancy 24. Hence, HCPs should be supported in developing consultation skills that elicit women’s pregnancy intentions, allow them to voice any concerns or anxieties, and foster a productive relationship for the delivery of PPC 32,33…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that empathy is a vital component of the helping relationship (Keefe, 1976;Reynolds & Scott, 1999) and enhances the well-being of those served (Hollinger-Samson & Pearson, 1999;LaMonica, Wolf, Madea, & Oberst, 1987;Olson, 1995). Unfortunately, we know very little about how empathy relates to students' choice of academic major and=or to interest in working with elders, although there is a small but persistent body of research that continues to link empathy and other related characteristics to students' choices of academic majors.…”
Section: Empathymentioning
confidence: 98%
“…The current study findings of moderate to high scores of empathy for infant pain (with means of greater than 45/100) are consistent with other studies conducted among nurses (24,34,35) and research reporting that nurses appraise infant procedural pain as higher than other clinicians (36,37). Some researchers have reported a relationship between nurses' self-reports of their empathy level and care outcomes (35,(38)(39)(40)(41), while other research findings indicate that no relationship exists (24,34). Several self-report measures have been developed and tested, and are reported to be reliable in measuring empathy, including the SPQ (30); however, the authors of a systematic review of nine studies exploring empathy in nurses and nursing students (37) concluded that there was considerable concern regarding the lack of psychometrically sound self-report instruments to measure this concept in nurses.…”
Section: Discussionmentioning
confidence: 99%